Farmers’ Perceptions of Agricultural Input Subsidies and Their Impact on Agricultural Productivity in Pokhara - Gautam, Arjun; Amgain, Pushpa Nidhi (Dhaulagiri Journal of Contemporary Issues, 2026)
This study aims to investigate farmers’ perceptions of agricultural input subsides and their impact on agricultural productivity in the context of the Prime Minister Agricultural Modernization Project (PMAMP). This study employed both descriptive and causal-comparative research designs and was conducted among 1,012 registered farmers in Pokhara Metropolitan City. The sample size was 212 using the Rao soft sample size calculator. A sample of 201 farmers was surveyed using purposive and snowball sampling design for the selection of the study area from 19 different wards. Primary data were collected through a structured survey questionnaire with five point Likert scale administered through both physical and online using Google forms. The collected data were analyzed using some descriptive statistics, correlation and multiple regression analysis. The findings of the study revealed that access to agricultural subsidies, access to credit and financial support, market proximity and infrastructure had significant positive effects on agricultural productivity, while land ownership status and regional disparities in subsidy allocation showed insignificant positive effect on agricultural productivity. In addition to, access to agricultural subsidies was the strongest predictor of agricultural productivity. Future research direction could be interventions needed to make input delivery methods, raise awareness and provide integrated support services.